Effects of combination drugs on antihypertensive medication adherence in a real-world setting: a Korean Nationwide Study. Issue 6 (22nd June 2019) - Kim, Seung Jae; Kwon, Oh Deog; Cho, BeLong; Oh, Seung-Won; Lee, Cheol Min; Choi, Ho-Chun
Abstract : Objectives: We tried to clarify, by using representative national data in a real-world setting, whether single-pill combinations (SPCs) of antihypertensives actually improve medication adherence. Design: A nationwide population-based study. Setting: We used a 2.2% cohort (n=1 048 061) of the total population (n=46 605 433) that was randomly extracted by National Health Insurance of Korea from 2008 to 2013. Participants: We included patients (n=116 677) who were prescribed with the same antihypertensive drugs for at least 1 year and divided them into groups of angiotensin II receptor blocker (ARB)-only, calcium channel blocker (CCB)-only, multiple-pill combinations (MPCs) and SPCs of ARB/CCB. Primary outcome measures: Medication possession ratio (MPR), a frequently used indirect measurement method of medication adherence. Results: Adjusted MPR was higher in combination therapy (89.7% in SPC, 87.2% in MPC) than monotherapy (81.6% in ARB, 79.7% in CCB), and MPR of SPC (89.7%, 95% CI 89.3 to 90.0) was higher than MPR of MPC (87.2%, 95% CI 86.7 to 87.7) (p<0.05). In subgroup analysis, adherence of SPC and MPC was 92.3% (95% CI 91.5 to 93.0) vs 88.1% (95% CI 87.1 to 89.0) in those aged 65–74 years and 89.3% (95% CI 88.0 to 90.7) vs 84.8% (95% CI 83.3 to 92.0) in those ≥75 years (p<0.05). According to total pill numbers, adherence of SPC and MPC was 90.9% (CI 89.8 to 92.0) vs 85.3% (95% CI 84.1 to 86.5) in seven to eight pills and 91.2% (95% CI 89.3 to 93.1) vs 82.5% (95% CI 80.6 to 84.4) in nine or more (p<0.05). The adherence difference between SPC and MPC started to increase at five to six pills and at age 50–64 years (p<0.05). When analysed according to elderly status, the adherence difference started to increase at three to four pills in the elderly (≥65 years) and at five to six in the non-elderly group (20–64 years) (p<0.05). These differences all widened further with increasing age and the total medications. Conclusion: SPC regimens demonstrated higher adherence than MPC, and this tendency is more pronounced with increasing age and the total number of medications.